A critical review of University of the Philippines Visayas (UPV) undergraduate research projects in history, 1998-2013. - Sanchez, Jessa Carmela C.
This paper is a critical review of the University of the Philippines (UPV) undergraduate research studies in History from 1998 to 2013. There are a total of 81 authored and co-authored undergraduate researches categorized under 1) Local History, 2) Political Biography, 3) Women Studies and 4) Social Movement. This study is critical about the knowledge production in the field of History discipline in the UPV Division of Social Sciences in the period of 15 years. Specifically, this paper aims to produce a range of topics and categories in the UPV undergraduate studies in History from 1998 to 2013, to examine the trends and development in the methods, theories and ways the undergraduate studies in History were written from 1998 to 2003 and to analyze the bearing of the social, economic and political issues and happenings from within the said time frame in the writings of the UPV undergraduate studies in History. A system of categorization was used to group together the 81 undergraduate studies in History with the same classification to create distinction on the topics in order to set the limitations on the studies. Tabular presentation using matrices on the basic information of the studies, methods, theories, advisors and the trends on national and local events were prepared for data analysis and interpretation. Library research utilizing books, journals, unpublished studies and other literatures dealing with critical review on history were also used as secondary data. The study found out that a huge concentration on studies dealing with local history were written in the past 15 years. Also, thesis advisorship has significantly affected the diversity of the studies. The undergraduate studies in History were also found to be silenced in response to the social, political and economic bearing.